(untitled) (Research, Society and Development, 2020)
The use of alternative teaching methodologies has been generating positive results in the teaching-learning process. Thus, science education needs to use teaching strategies that enhance students’ interest. The objective was to demonstrate that the use of these alternative didactic resources, through the use of drawings, which allies the theory promotes significant improvement in the understanding of the contents covered in science classes, having as its theme, the solar system. The work was developed by undergraduate students of the course of Biological Sciences of the Federal Institute of Rondônia during the conduction of the curricular regency, in which the activities were carried out with students from two sixth elementary school of a state school in the municipality of Ariquemes, Rondônia, and used the drawings as a teaching tool. It was observed that with the use of different resources and methodologies to approach the subject, students are more motivated and interested, and consequently became more active in the teaching-learning process. In addition, after the class can be seen that there was a significant increase in the amount of correctness in the amount and order of planets identified in the drawings of the students of both classes.